Analisis perhitungan, pemungutan, dan kontribusi pajak mineral bukan logam dan batuan terhadap pajak daerah dan pendapatan asli daerah Kota Tomohon - Pandi, Johanes Mishart; Elim, Inggriani; Weku, Priscillia (Yayasan Widyantara Nawasena Raharja, 2024)
The Non-Metallic Mineral and Rock Tax is a regional tax in Tomohon City that contributes to Regional Tax and Regional Original Income. This study will determine the mechanism for calculating and collecting Non-Metallic Mineral and Rock Tax in Tomohon City, as well as the contribution of Non-Metallic Mineral and Rock Tax to Regional Taxes and Original Regional Income of Tomohon City in the 2019-2023 period. This study employs a descriptive qualitative analysis method. The study results clearly show that the calculation and collection of Non-Metallic Mineral and Rock Tax in Tomohon City is based on the regulations in force in the region. The average contribution from 2019 to 2023 clearly demonstrates that the criteria for non-metallic mineral and rock tax contributions are very low, both for Regional Taxes and Regional Original Income. A comparison with other regional taxes shows that the contribution of non-metallic mineral and rock taxes to Tomohon Regional Taxes for the 2019-2023 period is either the highest or the lowest. It is clear that the contribution of non-metallic mineral and rock taxes to PAD is insignificant when compared to the total from other PAD sources. The decline in the contribution of non-metallic mineral and rock taxes in Tomohon City is influenced by two main factors: the awareness and honesty of taxpayers in calculating and paying their taxes, as well as committing other fraud that can harm the Tomohon City government. Changes in rules and policies also play a role. If managed properly, the potential contribution of non-metallic mineral and rock taxes in Tomohon City can be maximised.